2023
DOI: 10.3389/fsoil.2023.1137731
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and operation-induced instability of apparent soil electrical conductivity measurements

Abstract: Measuring apparent soil electrical conductivity (ECa), using galvanic contact resistivity (GCR) and electromagnetic induction (EMI) techniques, is frequently conducted to reveal spatial soil heterogeneity. Various studies have demonstrated the possibilities for significant changes in the measured quantities over time with relatively stable spatial structure representations. The objective of this study was to quantify the effects of temporal drift and operational noise for three popular ECa mapping instruments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By using an EMI device four times (Dualem 1S), Serrano et al [ 2 ] found temporally stable spatial EC a patterns in a Mediterranean pasture over a period of 7 years despite changing environmental and management conditions. Various studies have demonstrated the possibilities for significant changes in the measured EC a over time, nevertheless, with relatively stable spatial structure representations [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using an EMI device four times (Dualem 1S), Serrano et al [ 2 ] found temporally stable spatial EC a patterns in a Mediterranean pasture over a period of 7 years despite changing environmental and management conditions. Various studies have demonstrated the possibilities for significant changes in the measured EC a over time, nevertheless, with relatively stable spatial structure representations [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, relatively little is known about the degree of within-field spatial variation in soils used for livestock production, which leads to the common practice of uniform field 2 of 18 management [2]. Site-specific crop management aims to increase profitability and reduce the negative environmental impact of modern farming [7].…”
Section: Introductionmentioning
confidence: 99%
“…Soil EC is an important physicochemical parameter in the cultivation of agricultural plants because it reflects the content of minerals and salts dissolved in the soil, which in turn determines the ability of plants to absorb water. According to Mat Su and Adamchuk [40], the EC of soils is closely related to their salinity, texture and the CEC parameter. Optimal EC values for soil depend on the type of soil and crops grown, but are usually in the range of 500 to 3000 µS/cm.…”
Section: Chemical and Biological Factors Affecting Yieldsmentioning
confidence: 99%